Norwegian elite-level coaches: Who are they? - Fasting, K.; Sisjord, M. K.; Svela Sand, T. (Scandinavian Sport Studies Forum, 2017)
Previous studies have shown that there is an underrepresentation of female coaches and a lack of opportunities for women to coach males, particularly at the elite-level. Very few studies, however, have focused on elite-level coaches` demographics and whether these vary with respect to gender. The aim of this article is to get an overview of the gender distribution of Norwegian national team coaches with respect to different demographic variables, such as age, education and marital status. Furthermore, athletic background, coach education and coaching experience are examined. The results are based on data from an online survey among coaches who in 2012 worked as national team coaches (n=197). The main result is that the female and male coaches seem to be very similar, which is in contrast to the majority of previous research among elite-level female coaches. Another contradiction to previous studies, which mostly consist of qualitative research, is that the present quantitative study is based on a sample of national team coaches from all sports in Norway. Only 14% of the elite-level coaches are women. The explanation for this underrepresentation is discussed with respect to structural barriers that may be particularly relevant for elite-level coaching: sex-typing, stereotyping and homologous reproduction.